ADVANCEMENTS IN ORTHODONTIC MATERIALS: A REVIEW OF INNOVATIONS IN WIRES AND BRACKETS - Ebtisam Salman Al Saeed; Hassan Mohammed H Alharthi; Zahra Ali Al Ibrahim; Nahla Manie Alghamdi; Hussain Zaki Al Abdulwahhab; Mahdi Mordi Alanazi; Abdulaziz Ibrahim Aljabr; Essa Mohammed Hakami; Ghada Saad Saleh Alshohaib; Mislat Saad Almutairi; Faisal Hamad Alyahya (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Recent advancements in orthodontic materials, particularly in wires and brackets, have significantly enhanced both clinical outcomes and patient comfort. Innovations in materials such as nickel-titanium alloys and ceramic composites have brought forth improvements in mechanical properties and aesthetic qualities, meeting the rising patient demand for less conspicuous orthodontic devices. Enhanced flexibility, strength, and a more natural appearance characterize these new materials, contributing to their growing adoption in modern orthodontic practices. Technological enhancements in bracket design, driven by computer-aided design (CAD) and 3D printing, facilitate the production of customized brackets. These tailor-made solutions fit more precisely, reducing treatment time and improving patient comfort. Additionally, the use of digital technologies in treatment planning, including digital shavening and virtual simulations, has not only enhanced the predictability of treatment outcomes but also increased patient satisfaction and engagement. The introduction of softer and more adaptable wire materials has been pivotal in reducing the incidence of adverse effects such as root resorption, thereby improving the safety and comfort of orthodontic treatments. Emphasizing a patient-centered approach, the field of orthodontics now prioritizes materials that achieve effective results while satisfying aesthetic and comfort needs. The shift towards incorporating advanced materials and technologies marks a significant evolution in the field of orthodontics. Ongoing research and development are crucial for further improvements, ensuring that orthodontic treatment remains at the forefront of technological innovation. These developments not only promise more efficient, comfortable, and aesthetically pleasing treatment options but also underscore the importance of aligning clinical practice with patient expectations and well-being.